Momentum, Reversal, and Uninformed Traders in Laboratory Markets - BLOOMFIELD, ROBERT J.; TAYLER, WILLIAM B.; ZHOU, FLORA (HAILAN) (Journal of Finance, 2009)
ABSTRACT We report the results of three experiments based on the model of Hong and Stein (1999) . Consistent with the model, the results show that when informed traders do not observe prices, uninformed traders generate long‐term price reversals by engaging in momentum trade. However, when informed traders also observe prices, uninformed traders generate reversals by engaging in contrarian trading. The results suggest that a dominated information set is sufficient to account for the contrarian behavior observed among individual investors, and that uninformed traders may be responsible for long‐term price reversals but play little role in driving short‐term momentum.